2017
DOI: 10.2147/bctt.s130838
|View full text |Cite
|
Sign up to set email alerts
|

Alternative therapies for metastatic breast cancer: multimodal approach targeting tumor cell heterogeneity

Abstract: One of the primary challenges in developing effective therapies for malignant tumors is the specific targeting of a heterogeneous cancer cell population within the tumor. The cancerous tumor is made up of a variety of distinct cells with specialized receptors and proteins that could potentially be viable targets for drugs. In addition, the diverse signals from the local microenvironment may also contribute to the induction of tumor growth and metastasis. Collectively, these factors must be strategically studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…Since the activation of a pro-apoptotic response by chemotherapy can be affected by several factors, including cancer phenotypes and specific gene mutations, ultimately affecting the therapy success, the induction of alternative cell death pathway, alone or coupled to the apoptotic one [191], could represent an attractive goal in future anticancer intervention, especially in metastatic breast cancer cells [192,193]. The recent discovery of crosstalk connection among different cell death effectors and signalling pathways [194][195][196] will in fact offer novel effective therapeutic opportunities for targeted cancer therapies [197].…”
Section: Autophagy Activation In Breast Cancer Cellsmentioning
confidence: 99%
“…Since the activation of a pro-apoptotic response by chemotherapy can be affected by several factors, including cancer phenotypes and specific gene mutations, ultimately affecting the therapy success, the induction of alternative cell death pathway, alone or coupled to the apoptotic one [191], could represent an attractive goal in future anticancer intervention, especially in metastatic breast cancer cells [192,193]. The recent discovery of crosstalk connection among different cell death effectors and signalling pathways [194][195][196] will in fact offer novel effective therapeutic opportunities for targeted cancer therapies [197].…”
Section: Autophagy Activation In Breast Cancer Cellsmentioning
confidence: 99%
“…Breast cancer is a complex disease, involving tumor cells themselves and the tumor microenvironment, which includes multiple components of the extracellular matrix (ECM), such as collagen, as well as cellular components, such as fibroblasts (19,20). Many investigations have shown that CAFs play an important role in tumor initiation, progression, apoptosis and chemotherapy resistance (19,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…In a murine breast cancer model, TGF-beta exposure also enhances normal lung’s ability to better support establishment of breast cancer metastases 80. TGF-beta drives breast cancer’s EMT and various biochemical, morphological, and behavioral changes characteristic of EMT 10,8183. The manifold paths by which TGF-beta signaling leads to or enhances EMT specifically in breast cancer were outlined by Tan et al,18 Chen et al,81 Nooshinfar et al,84 and Felipe Lima et al75…”
Section: Drugs To Inhibit Emtmentioning
confidence: 99%